Tinjauan Sistematis Terhadap Metode Pengasuhan Pesantren Islamic Center Binbaz - Jawad Musyaffa’ Abdurrahman; Zulfikar Ihkam Al Baihaqi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
A pesantren is one of the oldest educational institutions in Indonesia, with the primary goal not only to enhance the thinking of its students but also their morality, ethics, and spirituality. Pesantren plays a crucial role in shaping the character of the students through education and upbringing that align with Islamic teachings, led by Kyai and Nyai. This upbringing aims to eliminate negative habits and internalize positive values. This research explores the methods of upbringing and social guidance in pesantren, particularly in creating a religious atmosphere. The methods applied include democratic, permissive, and authoritarian approaches, emphasizing discipline, responsibility, and character education. A case study at the Islamic Center Bin Baz Pesantren shows that this pesantren integrates formal and religious education, preparing students to become individuals of strong character who can contribute positively to society.